Cognitive impairment in patients with chronic heart failure and its impact on adherence to treatment - Yu. O. Aksenova; A. A. Petrukhina; Yu. F. Osmolovskaya; I. V. Zhirov; A. G. Beniashvili; M. A. Morozova; G. E. Rupchev; A. A. Galich; O. N. Tolstukhina; S. N. Tereshchenko (Терапевтический архив)
Aim. To evaluate cognitive impairment in patients with chronic heart failure (CHF) and its impact on treatment adherence.